Is rodent-borne Ljungan virus responsible for mortality in migrating Norwegian lemmings (Lemmus lemmus)? - Hauffe, Heidi Christine; Fevola, Cristina; Rossi, Chiara; Rizzoli, Annapaola; Niemimaa, J.; Henttonen, H. (country:DK, 2015)
In 1998, a new virus was isolated in wild populations of bank voles (Myodes glareolus) in Sweden. The suspected pathogen was named the “Ljungan virus” (LV), after the river near the site of its discovery. Later, it was also detected in voles in the United States and Denmark, and more recently in the UK and Italy. Interest in LV stems from reports that this virus may be associated with human fetal death and malformations. Some authors maintain that LV should be considered a potential zoonotic agent (i.e. a pathogen carried by wild animals that can infect and cause disease in humans), while others are distinctly more skeptical. Recent optimization and testing of a serological technique using LV-positive rodent samples show that humans can apparently be infected with LV, or an LV-type virus, but its ability to cause symptoms has not been definitively proven, and species-specificity has not been investigated.